2018
DOI: 10.1016/j.mec.2018.e00081
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic catabolism and respiratory lactate bypass in Ndh-negative Zymomonas mobilis

Abstract: Ability to ferment in the presence of oxygen increases the robustness of bioprocesses and opens opportunity for novel industrial setups. The ethanologenic bacterium Zymomonas mobilis performs rapid and efficient anaerobic ethanol fermentation, yet its respiratory NADH dehydrogenase (Ndh)-deficient strain (ndh-) is known to produce ethanol with high yield also under oxic conditions. Compared to the wild type, it has a lower rate of oxygen consumption, and an increased expression of the respiratory lactate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…In Z. mobilis , we observed a generalized increase, compared to baseline anaerobic growth, in the phosphorylation of most glycolytic enzymes during aerobic and N 2 -fixing growth conditions (Figure 3). The specific rate of glucose consumption changes substantially in these two growth conditions (Kremer et al, 2015; Strazdina et al, 2018), and it is possible that some of the phosphorylation events that we identified may regulate glycolytic enzyme activity leading to overall changes in flux.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Z. mobilis , we observed a generalized increase, compared to baseline anaerobic growth, in the phosphorylation of most glycolytic enzymes during aerobic and N 2 -fixing growth conditions (Figure 3). The specific rate of glucose consumption changes substantially in these two growth conditions (Kremer et al, 2015; Strazdina et al, 2018), and it is possible that some of the phosphorylation events that we identified may regulate glycolytic enzyme activity leading to overall changes in flux.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have indicated that during aerobic growth, oxidative damage to iron-sulfur (FeS) clusters constitutes a major factor influencing Z. mobilis metabolism and that respiratory enzymes and the ability to form multicellular aggregates are important for its survival (Jones-Burrage et al, 2019; Martien et al, 2019). Despite these and other recent advances (Yang et al, 2009; Rutkis et al, 2016; Strazdina et al, 2018), much remains to be learned about the regulation of Z. mobilis physiology during aerobic growth.…”
Section: Introductionmentioning
confidence: 99%
“…As a proof of principle, we tested whether we could efficiently delete an average size gene, choosing the 1.7 kb ldh gene encoding lactate dehydrogenase ( ldh , ZMO0256), since its function should be dispensable in Z. mobilis (Zou et al, 2012; Strazdina et al, 2018; Jones-Burrage et al, 2019). Our suicide plasmid (pPK15534) was engineered to contain two 500 bp sequences, immediately flanking but not including the target gene (pPK15535) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Existing genetic tools for Z. mobilis are not optimal for creation of strains with multiple engineered loci. A common approach to insertionally inactivate genes relies on host homologous recombination of an antibiotic resistance gene flanked by Z. mobilis DNA contained on a suicide plasmid, which, once integrated into the genome, can be screened for events leading to loss of delivery plasmid and gene of interest (Senthilkumar et al, 2004; Strazdina et al, 2018). This approach was enhanced by use of lambda red recombinase to increase the frequency of recombination events (Senthilkumar et al, 2004; Bo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another distinctive physiological characteristics of Z. mobilis is its high capacity of aerobic respiration, proceeding almost without concomitant energy production [3,[6][7][8]. The primary electron donor in Z. mobilis electron transport chain is NADH [9,10], therefore aerobic respiration results in acetaldehyde production by withdrawal of NADH from ethanol synthesis [3,11]. Yet the full scale of physiological consequences of aeration in Z. mobilis remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%